2007
DOI: 10.1088/0957-4484/18/31/315701
|View full text |Cite
|
Sign up to set email alerts
|

Is the molecular statics method suitable for the study of nanomaterials? A study case of nanowires

Abstract: Both molecular statics and molecular dynamics methods were employed to study the mechanical properties of copper nanowires. The size effect on both elastic and plastic properties of square cross-sectional nanowire was examined and compared systematically using two molecular approaches. It was found consistently from both molecular methods that the elastic and plastic properties of nanowires depend on the lateral size of nanowires. As the lateral size of nanowires decreases, the values of Young’s modulus decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…15,16 Based on the MD simulation with the LJ potential for copper, 13 it is found that the Young's modulus is not size-sensitive for the lateral dimension of the rod segments as shown in Fig. 3(a).…”
mentioning
confidence: 99%
“…15,16 Based on the MD simulation with the LJ potential for copper, 13 it is found that the Young's modulus is not size-sensitive for the lateral dimension of the rod segments as shown in Fig. 3(a).…”
mentioning
confidence: 99%
“…Jeng et al[39] compared molecular dynamics and molecular statics simulation of carbon nanotube under tension, and found that MS results are almost identical with MD results at 0.01K. Chang et al[40] reported similar findings.…”
mentioning
confidence: 83%